Phase transfer catalyst-assisted reversed-phase dispersive liquid–liquid microextraction for the rapid determination of organic acids in Fischer-Tropsch oil products. (1st September 2020) - Xie, Qilong; Sun, Dekui; Xia, Ming; Jia, Litao; Lu, Huaiqian; Shi, Hui; Hou, Bo; Li, Debao
Graphical abstract: Highlights: A phase transfer catalyst-assisted reversed-phase dispersive liquid–liquid microextraction has been developed. The extractant was 100 μL 0.1 M NaOH solution. A phase transfer catalyst (tetrabutylammonium bromide) acted as a dispersive agent. Preconcentration of 4 organic acids in Fischer-Tropsch oil products using proposed approach. Simplicity, low cost, short time and low LODs are advantages of the method. Abstract: A method prior to using high-performance liquid chromatography (HPLC), named phase transfer catalyst-assisted reversed-phase dispersive liquid–liquid microextraction (PTC-RP-DLLME), was developed for the rapid determination of organic acids in Fischer-Tropsch synthesis (FTS) oil products. This method used sodium hydroxide solution and tetrabutylammonium bromide (TBAB) as an extractant and a disperser respectively, in which the TBAB promoted the dispersion of aqueous NaOH solutions in the organic product, and acted as a hydrogen bond receptor to enhance the extraction of organic acids via hydrogen bond interactions. Under the optimized conditions, the calibration curves in the range of 0.1–30 μg mL −1 showed correlation coefficients (r) of 0.998–0.999. Detection limits (S/N = 3) were ranged from 1.0 to 3.5 ng mL −1 . The relative standard deviations of intra-day and inter-day repeatability were in the range of 2.9–5.8 % and 4.1–6.7%, respectively. The recoveries ranged from 85.4% to 105.9%. This developed method was employed for the analysis of organic acids in 6 types of oil products. This work provides an efficient and rapid pretreatment method for acid concentration prior to HPLC, and therefore saves time and cost for the quantitative analysis of FTS oil products. Moreover, precise analysis by application of this method is fairly beneficial to the FT catalyst improvement and industrial equipment material selection, and is rather significant for the proper design of the downstream processing/purification system.